XML Parser For SIP (Session Initiation Protocol) Message Bodies - Bajaj, Pavneet (My University, 2008)
In this we used RXP parser which is validating C Parser to parse SIP message bodies and include module for second level of validation of content type and integrate it with SIP Framework
M.E.(Software Engineering) Thesis
Keywords: VOIP; SIP; SAX; DOM Parser; RXP Parser